The chronification mechanism of orofacial inflammatory pain: Facilitation by GPER1 and microglia in the rostral ventral medulla - Zheng, Wenwen; Huang, Xilu; Wang, Jing; Gao, Feng; Chai, Zhaowu; Zeng, Jie; Li, Sisi; Yu, Cong (Frontiers in Molecular Neuroscience, 2023)
Background Chronic orofacial pain is a common and incompletely defined clinical condition. The role of G protein-coupled estrogen receptor 1 (GPER1) as a new estrogen receptor in trunk and visceral pain regulation is well known. Here, we researched the role of GPER1 in the rostral ventral medulla (RVM) during chronic orofacial pain. Methods and Results A pain model was established where rats were injected in the temporomandibular joint with complete Freund’s adjuvant (CFA) to simulate chronic orofacial pain. Following this a behavioral test was performed to establish pain threshold and results showed that the rats injected with CFA had abnormal pain in the orofacial regions. Additional Immunostaining and blot analysis indicated that microglia were activated in the RVM and GPER1 and c-Fos were significantly upregulated in the rats. Conversely, when the rats were injected with G15 (a GPER1 inhibitor) the abnormal pain the CFA rats were experiencing was alleviated and microglia activation was prevented. In addition, we found that G15 downregulated the expression of phospholipase C (PLC) and protein kinase C (PKC), inhibited the expression of GluA1, restores aberrant synaptic plasticity and reduces the overexpression of the synapse-associated proteins PSD-95 and syb-2 in the RVM of CFA rats. Conclusion The findings indicate that GPER1 mediates chronic orofacial pain through modulation of the PLC-PKC signal pathway, sensitization of the RVM region and enhancement of neural plasticity. These results of this study therefore suggest that GPER1 may serve as a potential therapeutic target for chronic orofacial pain.